2010
DOI: 10.1002/jccs.201000043
|View full text |Cite
|
Sign up to set email alerts
|

Metallopeptides — from Drug Discovery to Catalysis

Abstract: Oligopeptides are involved in diverse biological activities, including neurotransmission and antibiotic. Many natural-occurring peptides and peptide-ketide hybrids exhibit specific biological activities and chemical reactivities upon binding with certain metal ions, such as divalent metal-binding antibiotic bacitracin and anticancer Fe/Cu-bleomycin. There are also numerous synthetic peptides designed to bind metal ions to exhibit wide range of physical properties and chemical and biological activities. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 210 publications
0
14
0
Order By: Relevance
“…When these residues are present in α-helical peptides, they tend to occupy positions in the α-helix that are i ± 3 or i ± 4 relative to cationic residues, and it has been suggested that this structural positioning may promote helix formation via salt bridging and may be a strategy for improving the rigidity of α-helical residue arrangements and hence changing efficacy [181,182]. This use of metal ions to directly facilitate membrane interactions has also been reported for AAMPs from nonhuman sources [28,29] and other groups of AMPs such as the human antifungal CAMPs, histatins (Chapter 2) [183,184]. A similar metal-binding function appears to be served by serine residues, rendered anionic by phosphorylation, in the membrane interactions of peptide B/enkelytin and kappacins.…”
Section: Aamps and Their Structure-function Relationshipsmentioning
confidence: 92%
“…When these residues are present in α-helical peptides, they tend to occupy positions in the α-helix that are i ± 3 or i ± 4 relative to cationic residues, and it has been suggested that this structural positioning may promote helix formation via salt bridging and may be a strategy for improving the rigidity of α-helical residue arrangements and hence changing efficacy [181,182]. This use of metal ions to directly facilitate membrane interactions has also been reported for AAMPs from nonhuman sources [28,29] and other groups of AMPs such as the human antifungal CAMPs, histatins (Chapter 2) [183,184]. A similar metal-binding function appears to be served by serine residues, rendered anionic by phosphorylation, in the membrane interactions of peptide B/enkelytin and kappacins.…”
Section: Aamps and Their Structure-function Relationshipsmentioning
confidence: 92%
“…With this in mind, in this work, copper(II)-peptides mimicking the active site of laccase from Trametes versicolor were synthesized, characterized and used to catalyze oxidation and polymerization to degrade the aromatic and cyclic PhACs. Copper(II)-peptides are advantageous in terms of cost and stability as the copper in the short chain peptide forms additional stronger ionic and covalent bonds compared to hydrogen bonds in enzymes [ 12 , 13 ]. Peptides of longer chain are favoured for copper(II) binding compared to di- and tri-peptides as it needs to bind to more than one-metal binding amino acid such as histidine, aspartic acid, glutamic acid, cysteine and methionine to increase the stability of the complex [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most antibiotics do not need metal ions for their biological activity, there is a number of those called metalloantibiotics [2] that exhibit enhanced biological activity [3]. Some metal complexes exhibited remarkable antitumour, antifungal, antiviral, and other biological activities [1,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%